Voice and Leadership for Women in Fisheries to Actively Participate in Governance and Leadership Roles - Kilanga, Lucyphine; Kakwasha, Keagan; Kitogo, Lawrence; Simbila, Deogratius; Muzungaire, Lizzy; Lukanga, Editrudith; Mudege, Netsayi (WorldFish, 2024)
This report presents the outcome of the workshop with women on December 14th 2023 at Sanard Hotel. The main objective of the workshop was to empower women in the fisheries sector with the knowledge and skills required to actively participate in governance and leadership roles, thereby enabling them to raise their voices and contribute to decision-making processes in their communities. A total of 37 participants participated in the workshop, and these were drawn from various stakeholders, including women fish processors, Beach Management Units (BMUs), government authorities in the region, representatives from EMEDO, and WorldFish. The women fish processors at the workshop represented AWFISHNET’s country chapter, known as TAWFA.